2012
DOI: 10.3346/jkms.2012.27.1.36
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Number of Endoscopic Biopsies in Diagnosis of Advanced Gastric and Colorectal Cancer

Abstract: Endoscopic biopsy is necessary to confirm a histopathologic diagnosis. Currently, 6 to 8 biopsies are recommended for diagnosis of a suspected malignant lesion. However, multiple biopsies may result in several problems, such as an increased risk of bleeding, procedure prolongation, and increased workload to pathologists. The aim of this study was to clarify the optimal number of endoscopic biopsy specimens required in diagnosis of advanced gastrointestinal cancer. Patients who were diagnosed with advanced gast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
37
1
3

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 9 publications
0
37
1
3
Order By: Relevance
“…17,18 However, multiple biopsies posed some issues need to be remembered, such as high tendency to post procedure bleeding, increased time taken on endoscopy, and extra hour for examination by pathologists. 19 Some techniques may also be used in obtaining malignant tissue, such as brushing, aspiration, suction, salvage, and imprint cytology to improve the diagnostic yield of biopsy specimens in UGI malignancies. 12 gastric malignancy, especially those located in sub biopsy samples were only obtained by using forceps and only limited to the covering mucous.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 However, multiple biopsies posed some issues need to be remembered, such as high tendency to post procedure bleeding, increased time taken on endoscopy, and extra hour for examination by pathologists. 19 Some techniques may also be used in obtaining malignant tissue, such as brushing, aspiration, suction, salvage, and imprint cytology to improve the diagnostic yield of biopsy specimens in UGI malignancies. 12 gastric malignancy, especially those located in sub biopsy samples were only obtained by using forceps and only limited to the covering mucous.…”
Section: Discussionmentioning
confidence: 99%
“…Biopsies should be performed a sufficient number of times and in sufficient amounts. It has been reported that at least 3 or 4 biopsies from gastric cancer should be performed for a pathologic diagnosis [3] . In the present case, we performed biopsies to collect more than five specimens of ample amounts, despite the negative result.…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic biopsy has high sensitivity, with specificity [2] . The accuracy of biopsy can be increased by multiple-specimen collection and repeated performance [3] . In rare cases, endoscopic biopsies cannot reveal malignancy in patients with gastric cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Although the acquisition of six to eight biopsy specimens is recommended in Europe and the USA, 58 it has been reported in Japan and South Korea that there is no particular change in the diagnostic accuracy as long as at least two biopsy specimens are taken. 59,60 This difference may be derived from the fact that targeted biopsy from more suspicious areas based on endoscopic findings, rather than random biopsy from the entire lesion, is conducted in Japan. Unfortunately, biopsies have been conducted according to customary practice, and no studies have been carried out to examine the number of biopsy specimens desirable as a quality indicator for accurate diagnosis of gastric cancer.…”
Section: Knack Of Biopsymentioning
confidence: 99%